To solve for x, we need to simplify the equation first.
First, let's distribute the 6 to the expression inside the parentheses:
6(x) - 9 = 6x - 9
Now, we can simplify the equation further:
1/3 * (6x - 9) = -33
Multiplying 1/3 to the expression inside the parentheses:
(1/3) * 6x - (1/3) * 9 = -33
Simplifying:
2x - 3 = -33
Next, let's isolate the variable x.
Adding 3 to both sides of the equation:
2x - 3 + 3 = -33 + 3
Simplifying:
2x = -30
Finally, we divide both sides of the equation by 2 to solve for x:
(2x)/2 = (-30)/2
Simplifying:
x = -15
Therefore, x is equal to -15.
Solve for x.
1 over 3 (6 (x) − 9 ) = −33
1 answer